A Dél-tiszai identitásrégió kialakulásának első lépései - Kozma, József (Közép-Európai Közlemények, 2011)
All actors in Central-East Europe face the changing role of different regions. In Hungary, the regional policy of the new government recasts chances and duties of former development regions with primary focus on counties. The article deals with a specific region along Southern course of river Tisza. We prove that this part of a wider European region, a sometime organic one, is actually object of reintegration. We analyze different conditions and dimensions of altering relations which play eminent role in the reinforcement of the organic character. The perspective of local actors in the next period, can be found in he new European Danube Strategy, as long as they are ready to organize themselves on appropriate regional base. Danube Strategy will be filled with real content if each identity region will be ready to accommodate itself in the new and wider European structure of a functional macroregion called Danube Region. We conclude that appropriate management of conditions supports the ongoing European and inner integration process.